The effects of good governance and fraud prevention on performance of the zakat institutions in Indonesia: a Shariʿah forensic accounting perspective - Ika Sari Wahyuni-TD; Hasnah Haron; Yudi Fernando (Emerald Insight, 2024)
Indexed by WOS/SCOPUS/ERA